Preparo e caracterização de fibras adsorventes de íons Cu (II) à base de Eudragit® L100 via processo de eletrofiação - Silva, Ana Beatriz da (2021)
Many environmental and health problems are caused by toxic metal pollution in wastewater. One of these metals is the copper, and its accumulation in the human body can cause serious consequences. Various technologies have been developed for the treatment and removal of these metals, being the adsorption one of the most promising. To occur the adsorption process, it is necessary to use an adsorbent material. The adsorption is favored as the adsorbent presents large surface area. Thus, the use of fibers for adsorption can favor this process. Fibers can be developed in several ways, highlighting the electrospinning process that is considered of easy access and used in the development of thin fibers. For the development of fibers, this work used Eudragit® L100, an anionic copolymer derived from acrylic acid and methyl ester of methacrylic acid, and the solvents dimethylformamide (DMF) and ethanol (ETOH). The electrospinning process was optimized through factorial planning 22 of independent variables, with three repetitions at the central point. The experimental condition that promoted the smallest fiber diameter in the factorial design was 14% w/v Eudragit® L100 in solution, using 80% v/v ETOH (condition E14 (ETOH80)) in an ETOH / DMF mixture. This condition promoted thin fibers with an average diameter of 259 ± 53 nm. The fibers were characterized by scanning electron microscopy (SEM), the Fourier transform infrared spectroscopy with attenuated total reflectance (FTIR-ATR) and thermal analysis (DSC). Expansion and stability studies against dissolution in water have also been carried out. After the optimization of the process, adsorption studies were carried out toward Cu(II) ions. For the kinetic study, the model that best fitted the experimental data was the pseudo-second order. The fibers showed a maximum adsorption capacity (qe) of approximately 40 mg g-1 . A adsorption/desorption cycle confirmed that the fibers can be reused. Antimicrobial activity tests were also carried out. The Eudragit ® L100 fibers containing copper ions (sample E14/Cu) showed bacteriostatic activity against Pseudomonas aeruginosa (Gram-negative) and Staphylococcus aureus (Gram-positive). For the first time, the electrospinning process was optimized to obtain fibers based on Eudragit® L100, using the solvents dimethylformamide (DMF) and ethanol (ETOH), for use as a potential adsorbent for Cu (II) ions in aqueous media.